Case Report: Catheter-based mechanical thrombectomy using the Indigo aspiration system in a case of systemic-to-pulmonary shunt thrombosis - Soszyn, Natalie; Morgan, Gareth J.; Kim, John S.; Zablah, Jenny E. (Frontiers in Pediatrics, 2023)
A 53-day-old girl with absent right atrioventricular (AV) connection, malposed great vessels, and pulmonary atresia underwent placement of a central shunt on the sixth day of her life. Her postoperative course was complicated by progressive desaturation, and computed tomographic angiography (CTA) demonstrated near-complete occlusion of her left pulmonary artery (LPA). Angiography demonstrated a nonocclusive thrombus in the distal central shunt and a thrombus with complete occlusion of the LPA. The Indigo aspiration system (Penumbra) was used to remove the thrombus from the central shunt and LPA, allowing placement of a stent in the narrowed LPA. Subsequent angiography showed a wide patient central shunt and LPA. The Indigo aspiration system (Penumbra) provides a viable option for removing thrombus in a patients refractory to other methods.